The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1038/srep05311
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural screening of zebrafish using neuroactive traditional Chinese medicine prescriptions and biological targets

Abstract: The mechanism of the therapeutic action of antidepressants remains uncertain in traditional Chinese medicine (TCM). In this study, we selected 7 classical TCM prescriptions and utilised an automatic video-tracking system to monitor the rest/wake behaviour of larval zebrafish at 4 days post-fertilisation (dpf) for 48 hours. We found that the curative effects of the prescriptions were dose-dependent. K-means clustering was performed according to the shared behavioural phenotypes of the zebrafish. The results rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…Traditional Chinese Medicine (TCM), as a complementary and alternative medicine, has been proven to possess satisfactory effects against depression and its clinical complications. When treating depression, TCM starts from the whole body, considering not only the psychological problems that result from a patient's nervous system disorder but also the changes of the zang-fu organs, qi, and blood (Wang et al, 2014). Si-Ni-San (SNS), a famous formula, was first recorded in the "Treatise on Febrile Diseases" by Zhong-jing Zhang, a famous doctor in the Han Dynasty.…”
Section: Highlights Introductionmentioning
confidence: 99%
“…Traditional Chinese Medicine (TCM), as a complementary and alternative medicine, has been proven to possess satisfactory effects against depression and its clinical complications. When treating depression, TCM starts from the whole body, considering not only the psychological problems that result from a patient's nervous system disorder but also the changes of the zang-fu organs, qi, and blood (Wang et al, 2014). Si-Ni-San (SNS), a famous formula, was first recorded in the "Treatise on Febrile Diseases" by Zhong-jing Zhang, a famous doctor in the Han Dynasty.…”
Section: Highlights Introductionmentioning
confidence: 99%
“…Each compound was assigned a behavioural fingerprint and in each, different colours indicated the value of different behavioural parameters. By extracting the colour value (red, green and blue), the corresponding behavioural parameters were calculated (24). Among >500 compounds with significantly altered behaviour compared with controls, ~100 well-characterized compounds were selected for correlation analysis in the present study.…”
Section: Reverse Transcription-quantitative Pcr (Rt-qpcr)mentioning
confidence: 99%
“…Recently, Wang et al (2014) monitored the behavior of zebrafish larvae after exposure to radix ginseng by using an automatic video-tracking system. They found that the curative effects of the prescriptions were dosedependent.…”
Section: Chinese Ginseng Ashwagandha and Cannabinoidsmentioning
confidence: 99%